The Israel-Gaza Conflict in the British Press A Corpus-based Critical Stylistic Analysis - Hassan, Sawsan Hazim (Thi Qar Arts Journal, 2024)
This research investigates how corpus techniques incorporated into critical stylistics can contribute to representing the Israel-Gaza conflict in British broadsheet newspapers. The study indicates that the escalation of the Israel-Gaza conflict can be reflected differently and effectively in the language of news reporting. Examining collocations via the Sketch Engine tool provides a clear image of the representation of Israel, Gaza, and Hamas in the corpus under study. Collocational patterns contribute to representing the conflict and to discovering the positive and negative depictions exposed in the choice of language. These collocational patterns are further examined using the critical stylistic tool of naming and describing to demonstrate how Israel, Gaza, and Hamas are labelled and defined, portraying the ways the newspapers used to report the conflict during the selected period.The aim is to examine how topics related to the Israel-Gaza conflict are covered. The analysis was based on data from the British broadsheet newspapers The Times, The Guardian, The Daily Telegraph and The Independent. The research is swivelling around one primary question: What linguistic structures are employed to represent the Israel-Gaza conflict, and what thematic categories are identified via collocates? The results have revealed that the Israel, Gaza, and Hamas are portrayed differently. The occurrence of nominal choices shows that the three participants are labelled and described negatively. The basic categories observed are conflict, region, authority, and victimhood representing Israel, Gaza, and Hamas differently describing the real events as shown in the use of collocates from a wider textual-conceptual perspective exposed in the modifying and qualifying phrases.